Mengungkap Akar Fraud: Peran Internal Control, Ketaatan Akuntansi, Skema Imbalan, Ketimpangan Informasi dan Etika Manajerial - Ni Nyoman Ayu Suryandari; Sisilia Kartini (Ikatan Cendekiawan Muda Akuntansi (ICMA), 2026)
Fraud is an intentional act to obtain personal gain that harms others. This study aims to examine the effect of internal control, accounting compliance, reward schemes, information asymmetry, and managerial ethics on the risk of fraud in Village Credit Institutions (LPD) in Ubud District. The research sample consisted of 96 respondents selected through purposive sampling. Data were obtained through questionnaires and analysed using multiple linear regression. The results show that internal control, accounting compliance, and managerial ethics have a negative effect on fraud risk. This means that the stronger the internal control, accounting compliance, and managerial ethics, the lower the risk of fraud. Conversely, information asymmetry was found to have a positive effect on fraud risk, meaning that the greater the information asymmetry, the higher the risk of fraud. Meanwhile, the reward scheme did not show a significant effect on fraud risk. These findings indicate that fraud prevention in traditional financial organisations such as LPD needs to be supported by strong internal controls, information transparency, and high ethical values based on Tri Kaya Parisudha from its managers.